Empire Rainbow Alliance of the Deaf banner - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a banner that reads "Empire Rainbow Alliance of the Deaf" at the National March on Washington for Lesbian and Gay Rights.